Pengenalan dan Pemanfaatan Marketplace Shopee Untuk Meningkatkan Penjualan UMKM Kelurahan Sananwetan Kota Blitar - Wahyu Nurbayzura; Tuhfatul Ahbab; Nafisa Dean Putri Aqila; Intan Sulistyowati; Gagas Pandu Khrisna; Mentari Clara Dewanti; Ira Wikartika; Siti Aminah (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The development of information technology today is very sophisticated and rapid. The development of the internet in Indonesia is also increasing. Based on the survey results of the Indonesian Internet Service Providers Association (APJII), there are 210.03 million internet users in the country in the period 2021-2022. The service activity carried out by the 143 KKN-T MBKM UPN